The Eternal Return of Teaching in the Time of the Corporation. Issue 2 (May 2014) - Thompson, Greg; Cook, Ian
Abstract : This article addresses the new conditions under which teachers are making the choice to teach. Our core contention is that the reorganisation of schools according to the logic of the corporation, as described in Deleuze's 'Postscript', is changing the flows and forces on the primary surface of 'the classroom'. These changes block the usual movements of teaching to discipline, normalise and individualise, which was the role of the school as precursor to the factory. Blocked from repeating, or returning, teaching as it has always been done, teachers must actively re-will to teach; teachers cannot use order words to name themselves and direct flows and forces as they have usually been done. While many choices to teach will be undertaken, the most popular being that of choosing to teach toward the corporation, the repetition of teaching toward enclosed spaces becomes less compelling. Like Nietzsche's Zarathustra, teachers, who have the courage to actively choose, face a new dawn in which teaching cannot be what it once was. In that moment they must choose to repeat that choice an infinite number of times, the choice of eternal return, and it is from here that new times might begin.